Performance analysis and teaching analysis of the third movement of Beethoven's Moonlight Sonata (Op. 27 No. 2) - Xing, Kuan (Transactions on Social Science, Education and Humanities Research, 2024)
Ludwig Van Beethoven was a famous German composer and pianist who was a major musical figure in the transition from the classical period to the Romantic period. His 32 piano sonatas, characterized by profound thought, significantly contributed to the sonata form's structural development. Among his masterpieces, the "Moonlight Sonata" stands out for its rich emotional depth, innovative musical arrangement, and powerful musical effect that captivates the listener. The Presto agitato of the third movement imparts a sense of tension and excitement, as if immersing oneself in a storm of emotions. This rapid pace evokes an ineffable passion and impulse, crafting a musical universe that is both dynamic and profoundly emotional. This paper analyzes the third movement of the "Moonlight Sonata " from the perspectives of its creative background, musical structure, and performance techniques.